Additional mislabeling in African Onthophagus Latreille, 1802 (Coleoptera: Scarabaeidae: Scarabaeinae): the case of Onthophagus viviensis and Onthophagus laevatus - Rossini, Michele (Zootaxa, 2021)
The study of the type material of Onthophagus viviensis d’Orbigny, 1905 and Onthophagus laevatus d’Orbigny, 1902 (Coleoptera: Scarabaeidae: Scarabaeinae: Onthophagini) revealed that these two species described from Africa are instead two South American Onthophagus Latreille, 1802. The male of O. viviensis is described for the first time and its systematic position within the O. curvicornis species complex of American Onthophagus is discussed. In addition, Onthophagus laevatus new synonym is established as junior subjective synonym of Onthophagus curvicornis Latreille, 1812. Photographs of the type material examined, pictures of the body and male genitalia of O. viviensis and O. curvicornis, and an updated map of the geographic distribution of these two South American species is provided. A neotype is designated for O. curvicornis and lectotypes are designated for O. laevatus, O. minax Kirsch, 1866 and O. viviensis.